FEMINISME RADIKAL DALAM NOVEL NAYLA KARYA DJENAR MAESA AYU - Asrofah . (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2014)
The novel as a literary form part, is a universe reality in which events and behaviors experienced and done man (figure). Social reality, the psychological reality, religious reality, these terms are often heard when someone questions the novel as a reality of life. Specifically psychological reality as such, is the presence of certain psychological phenomenon experienced by the main character when responding or reacting to themselves and the environment. Feminism's core purpose is to improve women's status and the degree to match or align with the position and the degree of men. Feminist struggles and efforts to achieve this goal include a variety of ways. One way is to obtain the rights and opportunities equal to those of men. In that regard, then comes the term equal right's movement or motion persamaanhak. Another way is to free women from the bonds of the domestic environment or the family and household. This method is often called women's liberation movement, abbreviated women's lib or women's emancipation movement, the women's liberation movement. Novel written by Djenar Maesa Ayu Nayla very interesting when examined with a psychological approach, particularly in the analysis of frustration. This novel has the advantage of which is the story's main character was able and brave to face the various phenomena of life even though it has many conflicts. On the other hand, through the characters author wants to convey a moral message to the reader that the importance of parents to give good education to children.Keywords: feminism, psychological, novel